The influence of infant massage on urination patterns in babies aged 3-6 months receiving exclusive breastfeeding: A study at Bunda Patimah Primary Clinic - Paninsari, Debora; Dipa, Dara Sakinahtul; Gea, Rizki Ananda, Muliana; Nainggolan, Ines Novita Sarin (Priviet Social Sciences Journal, 2023)
Infant massage has been carried out in Indonesia since antiquity has been passed down from generation to generation without knowing how massage or touch has a positive impact on the human body. The touch part is the skin, which is the widest part of the human body, babies can feel this function from the womb. Micturition disorders occur due to impaired coordination function of the lower urinary tract including the bladder, bladder neck, valves and urethra. Urinary disorders including bed wetting with or without being followed by bowel obstructions, are disorders that are often found in children with all the consequences. Some complications due to urinary disorders are urinary tract infections, constipation and impaired healing of vesicoureteral reflux. In the process of urinating some babies will experience disturbances caused by delays in bladder maturation and development, sleep pattern disturbances, psychopathology, environmental stress, disturbances. To establish effectiveness of infants aged 3-6 months who receive massage and those who do not receive massage on the micturition patterns of infants exclusively breastfed at the Bunda Patimah Primary Clini. This research uses a type of quantitative research, namely an analytic surve. The research design used was cross- sectional. In this study, it was revealed whether there was an effect if massage was given or not to infants aged 3-6 months on micturition patterns. The chi-square test gives a value of p = 0.002 <0.05. This shows that the frequency of infant massage has an effect on urinary behavior in infants aged 3-6 months who are exclusively breastfed.